Roles of Non-Coding RNAs in Cervical Cancer Metastasis - Cheng, Tanchun; Huang, Shouguo (Frontiers in Oncology, 2021)
Metastasis remains to be a huge challenge in cancer therapy. The mechanism underlying cervical cancer metastasis is not well understood and needs to be elucidated. Recent studies have highlighted the diverse roles of non-coding RNAs in cancer progression and metastasis. Increasing numbers of miRNAs, lncRNAs and circRNAs are found to be dysregulated in cervical cancer, associated with metastasis. They have been shown to regulate metastasis through regulating metastasis-related genes, epithelial-mesenchymal transition, signaling pathways and interactions with tumor microenvironment. Moreover, miRNAs can interact with lncRNAs and circRNAs respectively during this complex process. Herein, we review literatures up to date involving non-coding RNAs in cervical cancer metastasis, mainly focus on the underlying mechanisms and highlight the interaction network between miRNAs and lncRNAs, as well as circRNAs. Finally, we discuss the therapeutic prospects.